Functional Phosphate Materials and Their Applications - Ameen, Sadia; Shaheer Akhtar, Mohammad; Shin, Hyung-Shik (IntechOpen, 2023)
All living things require phosphorus to survive. As such, it is crucial to investigate phosphate minerals from economic, agricultural, environmental, and health perspectives. The sustainability of human wellbeing on Earth depends on the ability to comprehend this critical resource and how we have used and abused it over time. This book examines the function of phosphate minerals in biology, human health and nutrition, food production, ecosystems, and environmental sustainability. It is a useful resource for readers from a range of backgrounds, including geologists and geochemists, lithologists, environmental scientists and engineers, chemists, and biochemists.